2012
DOI: 10.1002/bdrb.21027
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Response of Low Linear Energy Transfer X‐rays for Protection Against High Linear Energy Transfer Accelerated Heavy Ion‐Induced Teratogenesis

Abstract: Successful AR induction appears to be a radiation quality event, depending on the LET value and/or the particle species of the challenge irradiations. These findings would provide a new insight into the study on radiation-induced AR in utero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Rithidech and Scott [ 77 ] proposed that the protective mechanisms could be triggered in cells by a gamma-component that is produced within a body upon exposure to neutrons [ 78 ]. Additionally, it has been shown that low doses of low LET radiation may render resistance to genotoxicity and teratogenesis induced by high doses of HZE particles [ 75 , 79 ]. Intriguingly, priming normal human cells with low doses of energetic protons resulted in lower chromosomal damage induced by subsequent exposure to iron ions [ 80 ].…”
Section: Radiation Dna Damage and Mechanisms Of Repairmentioning
confidence: 99%
“…Rithidech and Scott [ 77 ] proposed that the protective mechanisms could be triggered in cells by a gamma-component that is produced within a body upon exposure to neutrons [ 78 ]. Additionally, it has been shown that low doses of low LET radiation may render resistance to genotoxicity and teratogenesis induced by high doses of HZE particles [ 75 , 79 ]. Intriguingly, priming normal human cells with low doses of energetic protons resulted in lower chromosomal damage induced by subsequent exposure to iron ions [ 80 ].…”
Section: Radiation Dna Damage and Mechanisms Of Repairmentioning
confidence: 99%
“…Prenatal LDIR exposure induces teratogenesis and mortality [5561] (Table 5). In female CF1 and BALB/c strain mice, irradiation with X-rays (100 mGy) at 7 h post fertilization resulted in increased frequency of malformed fetuses and Dwarfism occurrence when examined 18 days later.…”
Section: Ldir and Ldrir-induced Bionegative Effects In Animal Modelsmentioning
confidence: 99%
“…A single 10 mGy CT scan or PET scan (7–22 mSv) of Trp53 +/− female mice significantly extended the overall lifespan of these mice relative to the controls [92]. Primary conditioning with low doses of radiation was also reported to significantly suppress incidences of teratogenesis induced by a follow-on high dose of radiation [60, 61, 93]. In genetically susceptible ApoE −/− mice with normal p53 function, γ-radiation exposures at doses as low as 25 mGy, given at either an early or late stage of the disease, protected against atherosclerosis in a manner distinctly non-linear with respect to dose [94].…”
Section: Ldir/ldrir–induced Biopositive Effects In Animalsmentioning
confidence: 99%
“…In addition, teratogenic effects induced in fetal mice could be attenuated by an adaptive response using an X-ray priming dose followed by exposure to monoenergetic C-ions, neon ions, silicon (LET values 15, 30, 55 keV/μm) but not when using iron ions (200 keV/μm) for the challenge dose [ 241 , 242 ]. This suggests possible specific radiation quality effects of the challenge radiation.…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%